Prevalence of Diabetes Mellitus Among Pregnant Women Receiving Health Services at the Puerto Rico University Hospital, Puerto Rico, 1997-1998 - Acosta, Ivelisse; Aponte, Zuleyka; De Jesús, Zulma; De León, Ariel; González, María Del Carmen; Hernández, Johan; Martínez, Pablo; Santos, Esmirna R.; Pérez-Perdomo, Rosa (Puerto Rico Health Sciences Journal, 2013)
See manuscript